Computerized analysis of the distribution of occlusal contacts in individuals with Parkinson's disease and temporomandibular disorder. Issue 6 (1st November 2016) - Silva, Paula Fernanda da Costa; Motta, Lara Jansiski; Silva, Soraia Micaela; Ferrari, Raquel Agnelli Mesquita; Fernandes, Kristianne Porta Santos; Bussadori, Sandra Kalil
Objectives: The aims of the present study were to determine the prevalence of temporomandibular disorder (TMD) in a sample of patients with Parkinson's disease (PD) and to analyze the distribution of occlusal contacts. Method: The sample was composed of patients with PD aged 50–75 years. Temporomandibular disorder was evaluated using the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD). The distribution of occlusal contacts was determined using the portable T-Scan III ® occlusal analysis system during maximum voluntary clenching. Fisher's exact test was used to test the association between TMD and occlusal contact symmetry. Results: Forty-two individuals with PD were analyzed. The prevalence of TMD was 23.8%. No statistically significant association was found between TMD and occlusal contact symmetry. Moreover, no significant difference in the distribution of occlusal contacts was found between the groups with and without TMD. Discussion: The present data suggest no association between TMD and occlusal contact asymmetry in individuals with PD. Conclusion: The results of this study identified a prevalence of 23.8% of TMD signs in subjects with PD and a high frequency of occlusal asymmetry in this sample.